2014
DOI: 10.1016/j.jjcc.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Association of n-3 polyunsaturated fatty acids with soluble thrombomodulin as a marker of endothelial damage: A cross-sectional pilot study

Abstract: Although there are numerous unresolved issues in regard to the differences in the cardiovascular protective effects between EPA and DHA, DHA may be associated with a decrease in sTM. A large-scale trial would be warranted to demonstrate whether the beneficial effect of n3-PUFAs therapy on endothelial damage and improvement of endothelial function might also result in fewer clinical cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…7) It seems therefore likely that in vivo, EPA and DHA exhibit different physiological activities. [8][9][10][11] A strong positive correlation is known to exist between serum EPA and DHA levels, and this was also shown in our study cited above. [4][5][6] Because serum EPA and serum DHA levels serve as confounding factors for each other, there are limits to discussing their effects on the incidence of coronary artery disease.…”
supporting
confidence: 88%
“…7) It seems therefore likely that in vivo, EPA and DHA exhibit different physiological activities. [8][9][10][11] A strong positive correlation is known to exist between serum EPA and DHA levels, and this was also shown in our study cited above. [4][5][6] Because serum EPA and serum DHA levels serve as confounding factors for each other, there are limits to discussing their effects on the incidence of coronary artery disease.…”
supporting
confidence: 88%
“…Having said this, clinical trials on the effects of n-3 PUFA on endothelial function are significantly heterogeneous in number of included participants; inclusion criteria: age of participants, healthy or disease state, have been studied; markers of endothelial function: in addition to flow-mediated dilation, at least 7 different classes of surrogate markers have been tested in the last 5 years. The most frequent categories tested, according to their different pathophysiological roles, are proinflammatory and anti-inflammatory cytokines, endothelial progenitor cells, markers of platelet activation, of fibrinolysis, of thrombosis, and of coagulation, and markers of oxidative stress [ 98 102 ]; dose and duration of treatment: doses ranging from 0.45 up to 4 grams have been tested as well as treatments ranging from 4 to 52 weeks [ 58 , 103 , 104 ]; forms of n-3 PUFA: EPA, DHA, or ALA has been administered alone or in combination; concomitant therapy: most of the studies on disease states do not provide accurate information on concomitant therapy, particularly on drugs known to improve endothelial function such as statins and ACE inhibitors/angiotensin receptor blockers. The presence of a robust concomitant therapy might improve endothelial function independently of n-3 PUFA (especially at low doses) in high risk patients.…”
Section: N-3 Pufa and Endothelial Dysfunction: In Vivo Human Studimentioning
confidence: 99%
“…markers of endothelial function: in addition to flow-mediated dilation, at least 7 different classes of surrogate markers have been tested in the last 5 years. The most frequent categories tested, according to their different pathophysiological roles, are proinflammatory and anti-inflammatory cytokines, endothelial progenitor cells, markers of platelet activation, of fibrinolysis, of thrombosis, and of coagulation, and markers of oxidative stress [ 98 102 ];…”
Section: N-3 Pufa and Endothelial Dysfunction: In Vivo Human Studimentioning
confidence: 99%
“…In regression analysis, no significant associations between sTM levels and age, BMI or smoking habits were observed (Table 2). Previous studies showed inconsistent associations between these variables and sTM levels [47, 48, 51]. In our study, we did not include any older aged (>60 years) subject.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have considered age, sex, BMI, smoking and other characteristics as possible confounders for sTM [4651]. Dohi et al (2003) reported that sTM levels were higher in hypertensive patients than those of normotensive control group [52].…”
Section: Discussionmentioning
confidence: 99%